2013
DOI: 10.1308/003588413x13511609954653
|View full text |Cite
|
Sign up to set email alerts
|

Sernbo score predicts survival after intracapsular hip fracture in the elderly

Abstract: IntroductionThe Sernbo score uses four factors (age, social situation, mobility and mental state) to divide patients into a high-risk and a low-risk group. This study sought to assess the use of the Sernbo score in predicting mortality after an intracapsular hip fracture.MethodsA total of 259 patients with displaced intracapsular hip fractures were included in the study. Data from prospectively generated databases provided 22 descriptive variables for each patient. These included operative management, blood te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…(2013), who found the Sernbo score to be the only predictor of mortality (AUC =0.71, 95% CI: 0.65–0.76) with a sensitivity of 92% and a specificity of 51%. However, Dawe et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2013), who found the Sernbo score to be the only predictor of mortality (AUC =0.71, 95% CI: 0.65–0.76) with a sensitivity of 92% and a specificity of 51%. However, Dawe et al.…”
Section: Discussionmentioning
confidence: 99%
“…Such tools have been developed but none has been validated independently, and none is commonly used in clinical practice. 1,[7][8][9][10][11] One such tool is the Nottingham Hip Fracture Score (NHFS), 12 the use of which has been recommended by the Association of Anaesthetists of Great Britain and Ireland. 13 The score is calculated on the basis of age, gender, comorbidities, place of residence (i.e., home or institutional care), the abbreviated mental test score (AMTS) and the level of haemoglobin on admission.…”
mentioning
confidence: 99%
“…The Nottingham Hip Fracture Score (NHFS), the Sernbo Score, and the POSSUM system consider mortality (e.g., after 30 d or 12 mo) to be the outcome of interest. [ 9 , 12 , 25 ] In our opinion, an adequate treatment result is achieved if patients not only survive the first year after hip fracture but also maintain their independence. Thus, in contrast to previous studies, we defined a composite endpoint that consists of survival without being admitted to a nursing home.…”
Section: Discussionmentioning
confidence: 99%
“…Dawe et al also found only ASA 4 and 5 to be independent outcome factors. [ 25 ] Therefore, the predictive power of the ASA score is likely low when patients with mild systematic diseases (ASA 2) are compared with patients with severe systematic diseases (ASA 3). The ASA score itself is not part of the NHFS or POSSUM system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation